The teching task in educational institutions. The appropriation-alienation of the teacher’s work process in the context of the neoliberal educational reforms - Cornejo, Rodrigo (Revista de Psicología, 2006)
The aim of the present article is to analyze the teaching labour at schools, from the view of the processes of alienation and appropriation of the work (as process and as product).It will review the concepts of work and alienation raised by K. Marx and the contribution of G. Mendel to the problem of the appropriation of the act of work. It then analyzes the teaching tas, differentiating the product of the work, its process and the educational institution in which it takes place.Finally, it reviews the current context of neoliberal educational reforms in Latin America and the way in which may affect the educational labour, the teaching work and the processes of alienation and appropriation.